A hybrid probabilistic counter-based broadcast approach protocol for Mobile Ad hoc Networks. (19th March 2009) - Kathiravan, K.; Divya, V.; Thamarai Selvi, S.
Broadcast has been widely used in Mobile Ad Hoc Networks (MANETs) to disseminate information to all reachable nodes. However, the conventional broadcast scheme using simple flooding mechanism suffers from broadcast storm problem characterised by excessive amount of redundant traffic, exaggerated interference/contention between neighbouring nodes, and limited coverage. In this paper, we propose Probabilistic Counter Based Broadcast Protocol (PCBP) to alleviate broadcast storm problem in ad hoc networks. Compared with omni-directional scheme, PCBP uses minimum number of forward nodes to relay the broadcast packet. The proposed scheme is implemented in ns2 and the performances are compared against the conventional broadcast scheme.